Treatment of leg ulcers with autologous heparinized blood - Kaštelan, Marija (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1998)
Background. Human blood contains growth factors, which take part in wound healing. Objective. To test the hypothesis that topical application of human blood would improve ulcer healing, we have treated 26 leg ulcers of different etiology with repeated topical applications of human blood. Methods. Twenty-six ulcers were treated with autologous heparinized blood under the occlusive dressing every other day. Fifteen control were treated with antiseptic ointment. The duration of follow up for each patient was 3 weeks. The surface of the ulcers was measured by planimetry. The study was performed in patient at the Department of Dermatology, Rijeka. Results. The average surface reduction was 52.5% in ulcers treated by autologous heparized blood. On the contrary, in control ulcers the average surface reduction was 18.2%. Complete closure of the ulcer was obtained in 3 cases (11.5%). Ulcer surface was significantly reduced in ulcers treated autologous blood (p=0.001), compared to controls (p=0.62). Conclusion. Our results suggest that autologousheparinized blood stimulates cleasing and healing of the ulcers. it is well tolerated and an inexpensive method in the treatment of leg ulcers.
Keywords: Administration, topical; Blood; Drug therapy; Heparin; koža; Leg ulcer; noge; razjede; zdravljenje